Shakespeare in Japan’s zen philosophy: the plays of nothing at the theatre of nothing - Yoshio Arai (Ilha do Desterro)
Shakespeare and his colleagues built the Globe Theatre in 1599 with the wooden materials removed from the Theatre at Shoreditch. The first play performed on the stage of the newly built Globe is said to be Henry V. At the beginning of this history play, Chorus appears and asks the audience to exercise their imagination, as there is nothing in ‘this Wooden O’ but Shakespeare’s words, words, words. In other words, Shakespeare’s poetry is all on the stage of the Globe with only sunshine as natural stage lighting. Without sunshine, their performances were impossible. The sun is everything while the play is on, and nothing when the play is done. Moreover the Globe itself, like a Japanese Noh stage, was a bare stage without decorative or realistic stage settings.